Sintesis Nanopartikel Au-SiO2 Menggunakan Natrium Silikat dari Abu Ampas Tebu (AAT) - Nur Aini; Amaria Amaria (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
Synthesis of Au-SiO2 has been carried out using sodium silicate solution from bagasse ash (AAT) as the main source of silica. The purpose of this study was to determine the mole ratio of Au:Si in the relatively stable Au-SiO2 nanoparticles, which could be observed from the maximum wavelength and the determination of full width half maximum (FWHM). This type of research is experimental research. This research went through stages, namely synthesis of sodium silicate from bagasse ash, synthesis of Au-SiO2 and their characterization. The parameters studied were variations in the Au:Si mole ratio (1:19, 1:39 and 1:76), identifying the functional group Au-SiO2, determining the maximum wavelength and determining the stability of Au-SiO2. The identification of the Au-SiO2 was carried out using the FTIR instrument and the maximum wavelength was determined using a UV-VIS spectrophotometer. The results obtained are clear liquid Au-SiO2, dark red at a ratio of 1:19, pink at a ratio of 1:38 and 1:76. The results of identification with FTIR showed that the Au-SiO2 nanoparticles contained N-H and C-H groups at wave numbers 1566,77 cm-1 and 2923.02 cm-1, siloxane (Si-O-Si) and silanol (Si-OH) groups at wave numbers 1027.24 cm-1 and 902,12 cm-1. The results of measurements with a UV-VIS spectrophotometer show that Au-SiO2 nanoparticles are relatively stable at a ratio of 1:76 with a maximum absorption wavelength in the range of 523-523.5 nm, it can be said that silica was able to maintain the stability of Au nanoparticles in storage for 8 days. Key words: nanoparticle Au, silica, bagasse